Crystal structure of (1S, 2R, 4R, 9S, 11S, 12R)-9α-hydroxy-4, 8-dimethyl-12-[(thiomorpholin-4-yl)methyl]-3, 14-dioxatricyclo[9.3.0.02, 4]tetradec-7-en-13-one. (February 2015) - Benharref, Ahmed; Akssira, Mohamed; Ammari, Lahcen El; Saadi, Mohamed; Berraho, Moha
No abstract available